China and the Middle East since World War II a bilateral approach - Olimat, Muhamad (Lexington Books, 2014)
This comprehensive work on China and the Middle East addresses the increasing Chinese involvement in the Middle East and China's strategic interests in the region. It examines Sino-Middle Eastern relations based on a five-dimensional approach: political relations, trade ties, cultural relations, security coordination, and energy cooperation